1997
DOI: 10.1111/j.1349-7006.1997.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Intestinal Polyp Development by Nimesulide, a Selective Cyclooxygenase‐2 Inhibitor, in Min Mice

Abstract: Nonsteroidal anti‐inflammatory drugs (NSAIDs) suppress colon carcinogenesis in man and experimental animals. However, conventional NSAIDs inhibit both cyclooxygenase (COX) isoforms, COX‐1 and COX‐2, and cause gastrointestinal side‐effects. Nimesulide, a selective inhibitor of COX‐2, is much less ulcerogenic. We, therefore, examined its influence on the development of intestinal polyps in Min mice. Female Min mice at 4 weeks old were given 400 ppm nimesulide in their diet for 11 weeks. This treatment resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…These expression level changes of COX-2, iNOS, and adipocytokines, especially iNOS, could be associated with intestinal polyp development in Min mice. Indeed, it has been reported that iNOS inhibition, Pai-1 inhibition, COX-2 inhibition, and IL-6 knock out suppressed intestinal polyp development in Min mice (31,38,39,40). It has also been reported that 100-ppm atorvastatin treatment in Min mice slightly, but not significantly, reduced the activity and expression levels of COX-2 in the intestinal polyp (20).…”
Section: Discussionmentioning
confidence: 99%
“…These expression level changes of COX-2, iNOS, and adipocytokines, especially iNOS, could be associated with intestinal polyp development in Min mice. Indeed, it has been reported that iNOS inhibition, Pai-1 inhibition, COX-2 inhibition, and IL-6 knock out suppressed intestinal polyp development in Min mice (31,38,39,40). It has also been reported that 100-ppm atorvastatin treatment in Min mice slightly, but not significantly, reduced the activity and expression levels of COX-2 in the intestinal polyp (20).…”
Section: Discussionmentioning
confidence: 99%
“…34,35) We have also found an increase of cytokines and arachidonic acid cascade-related enzymes, phospholipase A 2 and COX-2, in rat colon carcinogenesis. 36 39) However, the mechanism by which COX-2 inhibitors suppress carcinogenesis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding has been that tumour incidence and multiplicity are reduced by both nonselective NSAIDs (Reddy et al 1993, Rao et al 1995, Boolbol et al 1996, Jacoby et al 1996, and selective COX-2 inhibitors (Table 3). In addition, those tumours that do develop in drug-treated animals tend to be reduced in size relative to those in control animals (Nakatsugi et al 1997, Fukutake et al 1998, Jacoby et al 2000a,b, Reddy et al 2000a. It is notable that selective COX-2 inhibitors appear to be at least as effective in preventing tumours as nonselective NSAIDs.…”
Section: Pharmacological Studies In Rodent Models Of Intestinal Tumormentioning
confidence: 99%